Quantitative analysis on the spatial characteristics of selected hospital nursing unit using space syntax theory - Albis, Erwin B. (College of Architecture, University of the Philippines Diliman, 2017)
This thesis quantitatively investigates what is the spatial structure of an efficient nursing unit layout. The study examines nursing unit characteristics such as the nurse station position, nursing unit size and shape, and the distance-to-bed-factor. Space syntax techniques using Visual Graph Analysis, Axial analysis, Mean Integration, Isovist Analysis, and Mean Depth are used on ten different nursing units. An investigation of the statistical attributes of these case studies is compared wtih the design metrics obtained from space syntax analysis. A survey was conducted for architects, doctors, and nurses to identify design criteria and preferred layout. The aim of this study is to propose key indicators to quantitatively measure, evaluate, and identify nursing unit plans by comparative analysis using Space syntax theory. The output of the study derives a reference tabulated guide that can be used as a Design Tool by hospital designers in preparing an efficient nursing unit. Designers can use this tool as a checklist reference or design options. Hospital administrators can also use this metrics in-case they decide to renovate their hospital in the future. This body of knowledge can be used as a practical way to test design alternatives of proposed nursing unit layout before it is constructed. This design metrics can also be used as a Design Tool to achieve Lean-Led hospital design.